Disease mapping for informing targeted health interventions: childhood pneumonia in Bohol, Philippines. Issue 11 (21st July 2015) - Thomas, Deborah S. K.; Anthamatten, Peter; Root, Elisabeth Dowling; Lucero, Marilla; Nohynek, Hanna; Tallo, Veronica; Williams, Gail M.; Simões, Eric A. F.; the ARIVAC Consortium; Mulholland, Kim; Klugman, Keith; Lansang, Mary Ann; et al.
Abstract Background Acute lower respiratory tract infections (ALRI) are the leading cause of childhood mortality worldwide. Currently, most developing countries assign resources at a district level, and yet District Medical Officers have few tools for directing targeted interventions to high mortality or morbidity areas. Mapping of ALRI at the local level can guide more efficient allocation of resources, coordination of efforts and targeted interventions, which are particularly relevant for health management in resource‐scarce settings. Methods An efficacy study of 11‐valent pneumococcal vaccine was conducted in six municipalities in the Bohol Province of central Philippines from July 2000 to December 2004. Geocoded under‐five pneumonia cases (using WHO classifications) were mapped to create spatial patterns of pneumonia at the local health unit (barangay) level. Results There were 2951 children with WHO‐defined clinical pneumonia, of whom 1074 were severe or very severely ill, 278 were radiographic, and 219 were hypoxaemic. While most children with pneumonia were from urban barangays, there was a disproportionately higher distribution of severe/very severe pneumonia in rural barangays and the most severe hypoxaemic children were concentrated in the northern barangays most distant from the regional hospital. Conclusions Mapping of ALRI at the local administrative health level can be performed relatively simply. If these principles are applied to routinely collected IMCI classification of disease at the district level in developing countries, such efforts can form the basis for directing public health and healthcare delivery efforts in a targeted manner.